Contribution of informal caregivers to self-care in individuals with heart failure - Mailson Marques de Sousa; Adriana Meira Tiburtino Nepomuceno; Rayana Pereira Feitosa; Lara de Sá Neves Loureiro; Renan Alves Silva; Maria das Graças Melo Fernandes; Simone Helena dos Santos Oliveira (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to evaluate the contribution of informal caregivers to the self-care of individuals with heart failure. Methods: a cross-sectional study was conducted with 87 caregivers from March to October 2022 in the city of João Pessoa/PB. The caregivers' contribution was assessed using the Caregiver Contribution to Self-Care of Heart Failure Index instrument. Scores ≥ 70 points indicate adequate contribution. Data were analyzed using descriptive statistics and Spearman's correlation. Results: the sample consisted of 81.6% female caregivers. Median scores obtained for the self-care contribution scales were: 63.3 for maintenance; 55.5 for management; and 66.6 for confidence. Caregivers never or rarely recommended monitoring body weight, regular physical exercise, extra use of diuretics, and fluid restriction. Conclusions: informal caregivers showed inadequate contribution in the areas of maintenance, management, and confidence in self-care of individuals with heart failure.